Indonesia’s Strategic Response to North–South Tensions: A Policy Analysis of Biodiesel Development during the Prabowo Administration - Arie Petra Levy; Sabrina Purwasantiana; Aulia Rasel Widodo; Nicholaus Harrison; Kayla Aqila Zahwa; Nayla Rizky; Zahira Alya (Badan Penerbit STIEPARI Press, 2025)
European Union regulations such as RED II that discriminate against CPO commodities produced by Southern countries, again reflect the tension between the North and South countries, especially on environmental issues. The study will analyze Indonesia's foreign policy strategy in responding to global pressure on CPO commodities through biodiesel policies, with a qualitative-descriptive approach and process tracing method. This study shows that by utilizing biodiesel as an instrument of energy diplomacy, Indonesia not only strengthens national energy security, but also strengthens Indonesia's bargaining position in international energy diplomacy, especially through South-South Cooperation. With Indonesia's adaptive response to EU pressure such as lawsuits to the WTO, diplomatic cooperation in international forums such as the G20, it indicates that through biodiesel policies Indonesia does not only focus on the technical dimension, but also the strategic dimension in fighting for Indonesia's national interest amidst systemic inequality.